The Effect of Human Resource Planning and Competence on the Performance of State Civil Apparatus in PPSDM of the Bukittinggi Regional Ministry of Home Affairs Through the Utilization of Information Technology During the Covid-19 Pandemic - Leo Agust Fernando; Heliyani (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to find out how the Effect of Huma Resource Planning and Competence on the Performance of State Civil Apparatus in PPSDM of the Bukittinggi Regional Ministry of Home Affairs through the utilization of Information Technology during the Covid-19 pandemic. The analysis technique used was SmartPLS 3.3 with a sample of 74 people. The results of the data analysis show that: 1) HR planning has a significant effect on the utilization of information technology in the PPSDM Kemendagri Regional Bukittinggi. 2) Competence has a significant effect on the utilization of information technology in the PPSDM of the Bukittinggi Regional Ministry of Home Affairs. 3) Human resource planning has a significant effect on state civil apparatus performance in PPSDM of the Bukittinggi Regional Ministry of Home Affairs. 4) Competence has a significant effect on state civil apparatus performance in PPSDM of the Bukittinggi Regional Ministry of Home Affairs. 5) Utilization of information technology has a significant effect on state civil apparatus performance in PPSDM of the Bukittinggi Regional Ministry of Home Affairs. 6) Human resource planning has a significant effect on state civil apparatus performance through the utilization of information technology in the PPSDM of the Bukittinggi Regional Ministry of Home Affairs. 7) Competence has an insignificant effect on state civil apparatus performance through the utilization of information technology in the PPSDM of the Bukittinggi Regional Ministry of Home Affairs.